Peel bond strength between 3D printing tray materials and elastomeric impression/adhesive systems: A laboratory study. Issue 7 (July 2020) - Xu, Y.; Huettig, F.; Schille, C.; Schweizer, E.; Geis-Gerstorfer, J.; Spintzyk, S.
Graphical abstract: Highlights: Peel bond strength between 3D printed tray materials and elastomers was studied. The tray materials showed good chemical compatibility with the elastomer adhesives. 3D printed tray materials could provide clinically adequate bond strength. Surface roughness generated by the AM technologies affected the bonding capacity. Generation of 3D printed surface topographies was clarified. Abstract: Objectives: The present study aimed to evaluate the bonding between three 3D printed custom tray materials and three elastomeric impression/adhesive systems using the peel test. Methods: Test blocks were 3D printed by three different technologies using Dental LT, FREEPRINT tray, and polylactide (PLA) tray materials. The reference test blocks were conventionally fabricated with Zeta Tray LC, a light-curing resin. The surface topographies of the four tray materials were investigated by scanning electron microscopy (SEM) analyses and roughness measurements. The peel bond strength between the four tray materials and three impression/adhesive systems, vinylsiloxanether (VSXE), vinyl polysiloxane (VPS), and polyether (PE), was measured ( n  = 12 per group). The peeling failure modes and rupture sites were identified microscopically. Results: The four tray materials featured different surface topographies. The peel bond strength was not significantly different with VSXE and PE, but PLA and the reference showed higher peel bond strength with VPS than the Dental LT and FREEPRINT tray ( p  < 0.05). The rupture site of adhesive failure in all groups was partly at the adhesive-impression material interface and partly within the adhesive but never at the adhesive-tray material interface. Significance: The 3D printed tray materials can achieve satisfactory chemical compatibility with the adhesives of VSXE, VPS, and PE. Surface topographies generated by the 3D printing technologies may affect bonding. Generally, 3D printed tray materials can provide clinically adequate bond strength with the elastomeric impression/adhesive systems. PLA is recommended for bonding with VPS when severe impression removal resistance is detected.